Dynamic Analysis of Hoist Cable Using Triangular Space-Time Elements - Witkowski, M. (Engineering Transactions, 1986)
In the paper the space-time element method with triangular net was used in order to examine how to control a drum of hoist so that the load hung on the end a cable moves in a definite manner. Taking the boundary conditions in consideration this problem becomes a nonlinear geometrical one. It was shown, that the space-time element method with triangular net leads to an uncoupled equations system, also when used for nonlinear geometrical problems.